Impacting green credit development on economic growth post-COVID-19 pandemic in vietnam - Quang Minh Nguyen; Hang Le Thi Thuy (Contemporary Economics, 2025)
The economy's growth contributes to the general development of social life but also severely impacts the environment. Since many countries worldwide are moving towards green growth, credit policies to serve green growth goals play a critical role. Many countries with different levels of development globally have pursued green credit policies, becoming a common development trend and an essential component of countries' sustainable development strategies. The use of green credit enables the bank to mitigate environmental and social risks associated with its commercial operations. Vietnam is slowly adopting this trend, but it still encounters several challenges and requires effective solutions to further stimulate this influx of capital. Thus, the article explores factors influencing Vietnam's green credit development and economic growth. This research applied the structural equation model (SEM) from surveying 750 commercial bank managers and collected it by convenient sampling. The data collection period was from September 2021 to December 2021. The study employed several methodologies to assess the dependability of Cronbach's alpha, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modeling (SEM) in order to evaluate the research hypotheses. The findings indicate that three factors have a significant impact, at a level of 1.0 percent, on the development of green credit and economic growth. Finally, the article novelty had several policy recommendations for developing green credit and economic growth in Vietnam.
Keywords: G00; G18; O10; O38; 330; green; credit; development; economy; growth